2012
DOI: 10.1523/jneurosci.3327-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Approaches Utilizing Oxytocin to Enhance Prosocial Behavior: From Animal and Human Social Behavior to Autistic Social Dysfunction

Abstract: ." This work is not meant to be a comprehensive review of oxytocin and prosocial behavior. Instead, we wish to share the newest findings on the effects of oxytocin on social behavior, the brain, and the social dysfunction of ASD at the molecular, genetic, systemic, and behavior levels, in varied subjects ranging from animal models to humans suffering from autism for the purpose of promoting further study for developing the clinical use of oxytocin in treating ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 155 publications
3
103
1
1
Order By: Relevance
“…Importantly, oxytocin has also been convincingly linked with protection from obesity [17][18][19][20][21][22][23]. While the nonapeptide oxytocin is historically recognized for its role in parturition [24] and lactation [25] it has gained more recent attention for its apparent effects on prosocial behavior [26,27] and therapeutic potential in the treatment of autism spectrum disorder (ASD) [26,27], schizophrenia [26,28] and obesity [17][18][19][20][21][22][23]. A large number of ongoing investigations in humans list oxytocin as the focus in studies on caloric intake, gastric emptying, or obesity, as displayed in the ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, oxytocin has also been convincingly linked with protection from obesity [17][18][19][20][21][22][23]. While the nonapeptide oxytocin is historically recognized for its role in parturition [24] and lactation [25] it has gained more recent attention for its apparent effects on prosocial behavior [26,27] and therapeutic potential in the treatment of autism spectrum disorder (ASD) [26,27], schizophrenia [26,28] and obesity [17][18][19][20][21][22][23]. A large number of ongoing investigations in humans list oxytocin as the focus in studies on caloric intake, gastric emptying, or obesity, as displayed in the ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…Medical crews during operation, soldiers in battle, or firefighters saving captives from flames-groups highly trained for coordinated performance-synchronize action within split seconds, and this ability has played a key evolutionary role in increasing the survival of our species under harsh conditions (Feldman, 2012;Yamasue et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…19,50-52 In addition, previous fMRI studies of TD participants have suggested that oxytocin's functional effects are observed particularly in regional activity and functional connectivity among the brain regions related to social cognition. 23 Considering these microscopic and mesoscopic findings, changes in activity and connectivity related to the mPFC may be an endophenotype that links oxytocin's behavioral effects with its influences on cellular and molecular systems.…”
mentioning
confidence: 99%